2022
DOI: 10.1029/2021ms002823
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Real‐Time 30‐s‐Update Big Data Assimilation System for Convective Rainfall Prediction With a Phased Array Weather Radar: Description and Preliminary Evaluation

Abstract: Radar observations are essential for capturing and predicting the evolution of convective precipitation. Numerous studies have assimilated radar observations to improve regional-scale analyses and forecasts (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Honda et al. (2022) briefly evaluated the performance of the real‐time SCALE‐LETKF during this event and showed that the real‐time SCALE‐LETKF successfully assimilated the MP‐PAWR observations every 30 s. This study further investigates the performance of the real‐time SCALE‐LETKF system by comparing with the JMA nowcast. Following Honda et al.…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Honda et al. (2022) briefly evaluated the performance of the real‐time SCALE‐LETKF during this event and showed that the real‐time SCALE‐LETKF successfully assimilated the MP‐PAWR observations every 30 s. This study further investigates the performance of the real‐time SCALE‐LETKF system by comparing with the JMA nowcast. Following Honda et al.…”
Section: Methodsmentioning
confidence: 88%
“…The system is called SCALE-LETKF first developed by Lien et al (2017). Recently, the SCALE-LETKF system has been extended by Honda et al (2022) to update real-time extended forecasts every 30 s with the assimilation of MP-PAWR observations. This study describes the application of the real-time version of SCALE-LETKF for a past precipitation event.…”
Section: Data Assimilation Systemmentioning
confidence: 99%
See 3 more Smart Citations